Dielectric tunability in (1-x)[Pb(Mg 1/3Nb 2/3)O 3]-xPbTiO 3 ceramics for tunable devices application - Guarany, C. A. (2010)
The dielectric properties of the 0.65[Pb(Mg 1/3Nb 2/3)O 3]-0.35PbTiO 3 ferroelectric ceramic composition were investigated viewing the capability to be used for tunable microwave applications. The dielectric response has been studied for three selected temperatures (300 K, 370 K and 400 K), below the paraelectric- ferroelectric phase transition temperature, as a function of the applied 'bias' electric field. The obtained dielectric tunability was found to be around 60 %, under an electric field of 19 kV/cm, which makes the studied ceramic composition an excellent candidate for application in the electro-electronic industry, as tunable devices. © 2010 IEEE.